Identifying Student Learning Motivation Towards Acid-Base Material Through STEM-Based Multimedia Learning Using Lumio - Diva Asriani; Kriswantoro Kriswantoro; Asrial Asrial; Damris Damris (FKIP - Universitas Riau, 2026)
This study aims to investigate the level of student motivation in learning acid-base material through the application of the STEM learning method enriched with Lumio interactive tools at SMA Negeri 11 Muaro Jambi. The method used is quantitative descriptive, involving students of class XI F1A as subjects. Information was collected using learning motivation questionnaire, which covered aspects such as learning independence, interest in acid-base topics, conceptual understanding, and enthusiasm during the learning process. From the analysis, the highest motivation score was 136 (Xmax), while the lowest was 116 (Xmin), with an ideal average of 126 (Mi) and an ideal standard deviation of 3.33 (SBi). Based on interval calculations, student motivation was categorized into five levels: Very High (if X > 130.99), High (127.67–130.99), Moderate (124.33–127.67), Low (121.01–124.33), and Very Low (if X < 121.01). The distribution results show that 50% of students are in the High category, 20% in Medium, 20% in Low, and 10% in Very Low. These findings indicate that the application of Lumio in STEM learning has a positive impact on increasing student learning motivation, as this interactive method is also effective in strengthening conceptual understanding and increasing interest in chemistry lessons.